FAO fisheries circular N.849 - Tacon, A G.J (FAO, 1992)
The document present an annotated list of 326 selected FAO field reports concerned with or containing relevant information on, the food and feeding of farmed fish and shrimp, including pond fertilization through direct or livestock integrtion, live food production, and artificial diet feeding. The reports presented were producted during the activities of 68 FAO field projects between 1973 and 1981. Reports are listed by project for individual countries or by region. Author, country and genera indexes are provided.